2012
DOI: 10.1259/bjr/25132680
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of liver tumours using hand-held real-time strain imaging: results of animal experiments

Abstract: Objective: Surgical resection is the only curative option for colorectal hepatic metastases. Intra-operative localisation of these metastases during hepatic resection is performed by intra-operative B-mode imaging and palpation. Because liver metastases are stiffer than normal tissues, elastography may be a useful complement to B-mode imaging. This paper reports quantitative measures of the image quality attained during intra-operative real-time elastographic visualisation of liver metastasis. Methods: VX2 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, another study by Inoue et al [ 14 ] on freehand RTE of live lesion in an intraoperative setting also reported similar effect mimicking “visual palpation”. Besides clinical research, an animal experiment [ 15 ] applying combined hand-held B-mode/strain imaging on rabbit hepatic metastases also provided valuable evidences for detection of liver metastases that might be missed by standard B-mode imaging alone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study by Inoue et al [ 14 ] on freehand RTE of live lesion in an intraoperative setting also reported similar effect mimicking “visual palpation”. Besides clinical research, an animal experiment [ 15 ] applying combined hand-held B-mode/strain imaging on rabbit hepatic metastases also provided valuable evidences for detection of liver metastases that might be missed by standard B-mode imaging alone.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to an extracorporeal device, an open procedure facilitates the protection of adjacent viscera and the intraabdominal staging of malignancies. The lesions not detected with preoperative imaging may be discovered intraoperatively 21,22 . Nevertheless, the use of an extracorporeal HIFU device is clinically feasible, as demonstrated by the treatment of hepatocellular carcinoma 23 , but only a small part (approximately 30%) of the liver is accessible using a noninvasive HIFU device unless a partial rib resection is performed 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies are available concerning its application to the liver, particularly for the evaluation of liver fibrosis. Apart from its use for characterization, RT elastography has been studied for the detection of liver nodules in animal models and during surgery [16,17] . In the latter setting, it has been demonstrated to have a higher diagnostic accuracy than B-mode intraoperative USS in detecting lesions surrounded by a heterogeneous background or with an iso echoic pattern (96% vs 89%).…”
Section: Elastographymentioning
confidence: 99%